Spontaneously Forming Oxide Layer of High Entropy Alloy Nanoparticles Deposited on Porous Carbons for Supercapacitors. Issue 1 (14th January 2021) - Shen, Enhui; Song, Xuehua; Chen, Qibin; Zheng, Mengmeng; Bian, Jianqing; Liu, Honglai
Abstract: High‐entropy alloy nanoparticles with a thin metal oxide layer, deposited onto hypercrosslinked polymer‐based carbon (HCPC), were synthesized through the adsorption of five metal ions in the hypercrosslinked polymers and subsequent in situ reduction of such ions (Fe 2+, Co 2+, Ni 2+, Cu 2+ and Sn 2+ ), followed by a carbonization process. The as‐prepared composites exhibit an excellent specific capacitance (495.4 F/g at 0.5 A/g in 1 M KOH), a superior cycling stability (94.7 % of initial capacitance after 15000 cycles at 10 A/g), and ultrafast charge transport kinetics (88.9 % fast kinetic capacitance at 200 mV/s). These excellent electrochemical behaviors are attributed to the pseudocapacitance of the metal oxide layer spontaneously formed on the outermost surface of the composite, having a thickness at the nanometer scale. Such findings suggest that this simple strategy, combining multimetallic nanoparticles with porous carbon materials, has promising potential to improve specific capacitance and paves the way to develop both the preparation of high‐entropy alloys and supercapacitors with improved performance. Abstract : On the surface : A new high‐entropy alloy nanoparticle/porous carbon composite is prepared, which is derived from the adsorption of five metal ions in hypercrosslinked polymers, the subsequent in situ reduction of such ions, and final carbonization. When exposed to air, the high‐entropy alloy nanoparticles can form a thin metal oxide layer on their outermost surfaces, which can thus be used as pseudocapacitor materials.